An annotated checklist and distribution of earthworms from Venezuela (Megadrili: Crassiclitellata) - Hernández-García, Luis Manuel; Sousa, Sandriel Costa; Ferreira, Carmen; Rousseau, Guillaume Xavier (Zootaxa, 2023)
An earthworm checklist has produced 78 nominal taxa (species/subspecies) of earthworm reported to date in Venezuela. The list of nominal taxa was obtained through literature review and the distribution maps were plotted by ecoregion. The 78 species/subspecies are divided into 24 genera and 6 families. Native earthworm species were more widely distributed than peregrine and exotic and are more associated with the conserved areas. Exotic species had been collected mainly in the north of the country in areas with at least some disturbance history. The peregrine species P. corethrurus is also widely distributed but with a preference for disturbed areas or related to its native natural grassland condition near the Guayana’s shield. This is the first accurate assessment of Venezuela’s earthworm species and subspecies in the last 14 years.